UV-curable adhesive composition

The ultraviolet curable adhesive composition, comprising polyfunctional urethane (meth)acrylate, N-vinylcaprolactam, and a photopolymerization initiator, addresses the challenge of achieving fast curing and strong adhesion to diverse materials, particularly with LED light sources, resulting in a versatile and effective adhesive for household use.

JP7671639B2Active Publication Date: 2025-05-02AICA KOGYO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021106221
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-28
Publication Date
2025-05-02
Estimated Expiration
2041-06-28

AI Technical Summary

Technical Problem

Existing ultraviolet curable adhesives do not achieve fast curing speeds and strong adhesion to a wide range of materials, including plastics and glass, especially when using LED light sources.

Method used

A polyfunctional urethane (meth)acrylate with an allophanate bond, combined with N-vinylcaprolactam and a photopolymerization initiator, including acylphosphine oxide, forms an ultraviolet curable adhesive composition with a specific solids content range.

Benefits of technology

The adhesive composition exhibits extremely fast curing speeds and strong adhesion to various materials, including plastics and glass, even with LED light sources, making it suitable for household use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671639000001
    Figure 0007671639000001
  • Figure 0007671639000002
    Figure 0007671639000002
  • Figure 0007671639000003
    Figure 0007671639000003
Patent Text Reader

Abstract

To provide a UV-curable adhesive that can be cured very quickly even using an irradiation device with an LED light source, and has strong adhesion to a wide range of materials such as glass, including plastic such as ABS.SOLUTION: A UV-curable adhesive composition contains a polyfunctional urethane (meth)acrylate having an allophanate bond, an N-vinyl compound, and a photopolymerization initiator. The content of the N-vinyl compound relative to the total solid content is 15-45 wt.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ultraviolet-curable adhesive composition. [Background technology]

[0002] There has been a great demand for adhesives that harden in a short time at room temperature, and known types of adhesives include two-component fast-curing epoxy resins, instant adhesives, anaerobic adhesives, etc. Among these, two-component fast-curing epoxy resins require the measurement of the base resin and hardener, and anaerobic adhesives have the problem that the parts that come into contact with air do not harden. In addition, both of them have a short hardening time, but they require at least several tens of seconds to several minutes.

[0003] In this respect, instant adhesives, mainly cyanoacrylate-based ones, can harden in a few seconds, and are therefore widely used as general adhesives for household use. On the other hand, when the materials are plastic and the contact area between them is small, the hardening time is long and the adhesive strength is low. In addition, there is a problem that the area near the adhesive part of the plastic material will turn white due to the vapor of the cyanoacrylate.

[0004] On the other hand, as adhesives that cure in a short time other than these resins, a method of curing acrylic or epoxy resins with ultraviolet light is known. However, since these methods require an ultraviolet light irradiation device, they have been used more for industrial purposes than for general household use. However, recently, easy-to-use ultraviolet light irradiation devices for household use have become commercially available, and the applications of ultraviolet-curing resins have expanded (Patent Document 1). For a wide range of adherends, including glass, wood, metal, and plastics such as ABS, ultraviolet-curing adhesives that cure quickly even with an irradiation device using an LED light source and have strong adhesive strength are now required. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6335853 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides an ultraviolet-curing adhesive that has a very fast curing speed even when used with an LED light source irradiation device and has strong adhesive strength for a wide range of materials, including plastics such as ABS, as well as glass. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention relates to a polyfunctional urethane (meth)acrylate (A) having an allophanate bond, N-Vinylcaprolactam The present invention provides an ultraviolet-curable adhesive composition comprising (B) and (C) a photopolymerization initiator, the amount of (B) being 15 to 45% by weight based on the total solid content.

[0008] The invention of claim 2 is Further, the (meth)acrylate monomer (D) having a phosphate ester group is included. The ultraviolet-curable adhesive composition according to claim 1 is provided.

[0009] The invention of claim 3 is The (C) contains an acylphosphine oxide (c1), and the amount of (c1) is 0.3 to 7 parts by weight based on 100 parts by weight of the photocurable component. 3. The ultraviolet-curable adhesive composition according to claim 1, wherein the ultraviolet-curable adhesive composition is a fluororesin.

[0010] The invention of claim 4 is Further containing reactive diluent (E) The present invention provides an ultraviolet-curable adhesive composition according to any one of claims 1 to 3. Effect of the Invention

[0012] The ultraviolet-curable resin composition of the present invention cures very quickly even with an irradiation device using an LED light source, and has strong adhesive strength to a wide range of substrates such as plastics and glass, making it useful as an ultraviolet-curable adhesive that can be used in ordinary households. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below.

[0014] The composition of the present invention is composed of a polyfunctional urethane (meth)acrylate (A), an N-vinyl compound (B), and a photopolymerization initiator (C). In this specification, the term "(meth)acrylate" includes both acrylate and methacrylate.

[0015] The polyfunctional urethane (meth)acrylate (A) used in the present invention is one of the main components constituting the cured film, and has abrasion resistance and toughness due to the cohesive force of hydrogen bonds derived from urethane bonds. The urethane bond has an allophanate bond (-NH-CO-NCOO- group) in which the urethane bond reacts with an isocyanate group, and the interaction of hydrogen bonds between OH groups, which has a large effect on the viscosity, is intramolecular, so that it is possible to lower the viscosity compared to urethane (meth)acrylates of the same structure that do not have allophanate bonds. In addition, even in thick films, it has good curing properties with a fast curing speed and no stickiness, and is characterized by high hardness and low curing shrinkage. The number of functional groups is preferably 2 to 6, and more preferably 3 to 4. By setting it in this range, the curing shrinkage during curing can be reduced, and the adhesion to the adherend can be more stabilized.

[0016] The weight molecular weight (hereinafter referred to as Mw) of (A) is preferably 400 to 3,000, more preferably 500 to 2,000, and particularly preferably 600 to 1,000. By making it 400 or more, the cohesive force of the cured product can be sufficiently ensured, and by making it 3,000 or less, the composition viscosity can be easily adjusted to a suitable level for workability. Note that Mw was measured and calculated by gel permeation chromatography using a column with a styrene-divinylbenzene-based packing material and a tetrahydrofuran eluent as the molecular weight in terms of standard polystyrene.

[0017] The amount of (A) is preferably 20 to 84% by weight, more preferably 23 to 82% by weight, particularly preferably 40 to 81% by weight, and most preferably 45 to 80% by weight, based on the total amount of solids in the composition. By making it 20% by weight or more, sufficient curability can be ensured, and by making it 84% by weight or less, sufficient adhesive strength can be ensured for various adherend materials. Examples of commercially available allophanate bond-containing urethane (meth)acrylates include EBECRYL 4738, EBECRYL 4740, and EBECRYL 4666 (trade names: manufactured by Daicel-Allnex Corporation).

[0018] The N-vinyl compound (B) used in the present invention is blended for the purpose of improving the adhesive strength with the adherend and improving the reaction curing property. For example, N-vinylcaprolactam, N-vinylpyrrolidone, N-vinylcarbazole, N-vinylpyridine, N-vinylacetamide, N-vinylformamide, N-vinylimidazole, N-vinylmorpholine, N-vinylsuccinimide, etc. can be mentioned, and they can be used alone or in combination of two or more kinds. Among these, N-vinylcaprolactam is preferred because it has low viscosity, good compatibility with (A), and is easily available.

[0019] The amount of (B) is 15-45% by weight, preferably 18-40% by weight, and more preferably 20-35% by weight, based on the total amount of solids in the composition. If it is less than 15% by weight, it becomes difficult to ensure sufficient adhesive strength, and if it exceeds 45% by weight, it becomes difficult to ensure sufficient adhesive strength due to the reduced flexibility of the cured film. Commercially available N-vinyl compounds include V-cap (trade name: N-vinyl caprolactam, manufactured by Ashland).

[0020] The photopolymerization initiator (C) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, 2.2-dimethoxy-1.2-diphenylethan-1-one is a benzyl ketal type, 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one are α-hydroxyacetophenone types, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one is an α-aminoacetophenone type, and 2.4.6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2.4.6-trimethylbenzoyl)-phenylphosphine oxide are acylphosphine oxide types, which can be used alone or in combination of two or more. Among these, it is preferable to mix the acylphosphine oxide type (c1), which has excellent internal curing properties.

[0021] The amount of (c1) is preferably 0.3 to 7 parts by weight, more preferably 1 to 5 parts by weight, based on 100 parts by weight of the radical polymerizable component. By adding it in this range, the composition can be cured efficiently. The amount of (C) including (c1) is preferably 0.3 to 10 parts by weight, more preferably 1 to 5 parts by weight, based on 100 parts by weight of the radical polymerizable component. Commercially available products of (c1) include Omnirad TPO and Omnirad 819 (trade name: manufactured by IGM Resins).

[0022] In the present invention, it is preferable to further blend a (meth)acrylate monomer (D) having a phosphate ester group. (D) is blended for the purpose of improving the adhesive strength with metals and glass. The mechanism by which the adhesive strength is improved is believed to be that the adhesion is improved by ionic interactions between the phosphate group in the component and the metal, metal oxide, and glass interface.

[0023] Examples of (meth)acrylate monomers having a phosphate group include 2-(meth)acryloyloxyethyl dihydrophosphate, dipentaerythritol penta(meth)acryloyloxydihydrogen phosphate, etc. In particular, bis[2-(methacryloyloxy)ethyl] hydrogen phosphate of the following chemical formula (1), which is produced by reacting 2-hydroxyethyl methacrylate with phosphoric anhydride, is preferred. Chemical formula (1) JPEG0007671639000001.jpg81135

[0024] The amount of (D) is preferably 5% by weight or less, more preferably 2% by weight or less, based on the total amount of solids in the composition. By adding it in this range, the adhesive strength can be further improved compared to when it is not added. Commercially available (meth)acrylate monomers having a phosphate ester group include KAYAMER PM-2 and PM-21 (trade names: manufactured by Nippon Kayaku Co., Ltd.).

[0025] In the present invention, a reactive diluent (E) may be further blended. From the viewpoint of suppressing cure shrinkage, it is preferably bifunctional or less, and more preferably monofunctional. For example, examples of chain alkyl monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, examples of alicyclic monomers include cyclohexyl (meth)acrylate and isobornyl (meth)acrylate, and examples of monomers having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-methylethyl (meth)acrylate, and 2-methylethyl (meth)acrylate. Examples of the monomers having an aromatic ring include benzyl (meth)acrylate, phenoxyethyl acrylate, and methylphenoxyethyl acrylate. Examples of the amide compounds include N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and acryloylmorpholine. These can be used alone or in combination of two or more. Among these, isobornyl acrylate is preferred because it has good compatibility with (A) and (B), is highly dilutable, has a high Tg, is good scratch resistance, and is low in skin irritation.

[0026] The amount of (E) is preferably 40% by weight or less, more preferably 35% by weight or less, based on the total amount of solids in the composition. By making it 40% by weight or less, it is possible to obtain a viscosity with excellent workability, ensure sufficient reaction curing, and improve adhesive strength.

[0027] In addition, the present composition may further contain additives such as adhesion promoters, light stabilizers, polymerization inhibitors, wetting agents, antioxidants, curing assistants, silane coupling agents, plasticizers, sensitizers, defoamers, flame retardants, inorganic fillers, organic fine particles, colorants such as pigments, dyes and colorants, antibacterial agents and antiviral agents, as long as the performance is not impaired.

[0028] The light stabilizer is blended to suppress the increase in viscosity during storage. Examples include hindered amines, hindered phenols, phosphites, and thioethers, and may be used alone or in combination of two or more. The blending amount per 100 parts by weight of the photoreactive component is preferably 0.2 to 2.0 parts by weight, more preferably 0.5 to 1.5 parts by weight. Commercially available hindered amine products include Tinuvin 249 (trade name: manufactured by BASF Japan).

[0029] The polymerization inhibitor can be blended to prevent thickening and improve storage stability. Examples include pyrocatechol, hydroquinone derivatives, dibutylhydroxytoluene (hereinafter referred to as BHT), etc., which can be used alone or in combination of two or more. The blending amount of the polymerization inhibitor is preferably 3% by weight or less, more preferably 1% by weight or less, based on the total solid content.

[0030] The present invention will be described in detail below with reference to examples and comparative examples, but these are merely illustrative examples and are not intended to be limiting. The amounts blended are in parts by weight, and unless otherwise indicated, measurements were taken at room temperature of 25°C and relative humidity of 65%.

[0031] Example 1 The ultraviolet-curable adhesive composition of Example 1 was prepared by mixing the components as shown in Table 1 until uniformly dissolved, using EBECRYL4738 (trade name: Daicel-Allnex Corporation, trifunctional allophanate type, Mw800) as (A), V-cap (trade name: Ashland Corporation, N-vinylcaprolactam) as (B), and OmniradTPO (trade name: IGM Resins Corporation, 2.4.6-trimethylbenzoyl-diphenyl-phosphine oxide) as (C) in the composition shown in Table 1.

[0032] Examples 2 to 12 In addition to the materials used in Example 1, KAYAMER PM-2 (trade name: Nippon Kayaku Co., Ltd., 2-methacryloyloxyethyl dihydrophosphate) was used as (D), Light Acrylate IB-XA (trade name: Kyoeisha Chemical Co., Ltd., isobornyl acrylate) and DEAA (diethylacrylamide) were used as (E), Tinuvin 249 (trade name: BASF Japan, neutral hindered amine type) was used as a light stabilizer, and BHT was used as a polymerization inhibitor. The ultraviolet-curable adhesive compositions of Examples 2 to 12 were prepared by stirring until uniformly dissolved in the formulation shown in Table 1.

[0033] Comparative Examples 1 to 5 In addition to the materials used in the examples, EBECRYL4513 (product name: Daicel-Allnex Corporation, trifunctional aliphatic urethane acrylate, Mw2000) was used as an oligomer, and the ultraviolet-curable adhesive compositions of Comparative Examples 1 to 5 were prepared by stirring until uniformly dissolved in the formulation shown in Table 2.

[0034] Table 1 JPEG0007671639000002.jpg52135

[0035] Table 2 JPEG0007671639000003.jpg90135

[0036] The evaluation method was as follows.

[0037] Storage stability: 20 g of the adhesive composition was placed in a glass bottle, sealed, and left for 24 hours in an environment of 25°C. If no gelation, precipitation of the compound, layer separation, whitening, etc. occurred, it was marked as ◯, and if any of the following occurred, it was marked as ×.

[0038] Curability: The adhesive composition was placed in a 10 mm x 10 mm silicone container to a thickness of 3 mm, and cured by irradiating it for 60 seconds at an output of 12 mW / cm2 (wavelength 405 nm) using a 6 W LED-UV irradiation device made by Elber. The surface of the cured product was checked by touch for stickiness, with no stickiness marked as ○ and present stickiness marked as ×.

[0039] Adhesive strength: The adhesive composition was applied to a 1 mm thick white glass plate to a thickness of 200 μm and a diameter of 5 mm, and a 1 mm thick ABS sheet was attached thereon and photocured from the glass side under the same conditions as above. The ABS surface was then fixed with a jig, and the glass surface was vertically raised at a crosshead speed of 5 mm / min. to measure the maximum strength at the time of peeling, with 1.0 MPa or more being rated as ◎, 0.5 MPa or more but less than 1.0 MPa being ◯, and less than 0.5 MPa being ×.

[0040] Evaluation results Table 3 JPEG0007671639000004.jpg27135

[0041] Evaluation results Table 3 JPEG0007671639000005.jpg56135

[0042] Each of the formulations in the Examples was satisfactory with no problems in terms of storage stability, curing property, and adhesive strength.

[0043] On the other hand, Comparative Examples 1 and 2, in which (B) exceeds the upper limit, had low adhesive strength, and Comparative Example 1, in which the blending amount of (B) was high, also had poor storage stability. Comparative Examples 3 and 4, in which (B) was not blended, also had low adhesive strength, and Comparative Example 4 in particular had poor curing properties, and Comparative Example 5, in which an oligomer having no allophanate bond was blended instead of (A), had insufficient curing properties, and none of the blends were suitable for the present invention.

Claims

1. An ultraviolet-curable adhesive composition comprising (A) a polyfunctional urethane (meth)acrylate having an allophanate bond, (B) N-vinylcaprolactam, and (C) a photopolymerization initiator, the amount of (B) being 15 to 45% by weight based on the total solid content.

2. 2. The ultraviolet-curable adhesive composition according to claim 1, further comprising a (meth)acrylate monomer (D) having a phosphate group.

3. 3. The ultraviolet-curable adhesive composition according to claim 1, wherein the (C) contains an acylphosphine oxide (c1), and the amount of the (c1) is 0.3 to 7 parts by weight per 100 parts by weight of the photocurable component.

4. 4. The ultraviolet-curable adhesive composition according to claim 1, further comprising a reactive diluent (E).

Citation Information

Patent Citations

  • Metal shuttle of air jet type loom

    JP1988035853A

  • Resin composition for protective coating and adhesion of dvd

    JP1999073684A

  • Adhesive composition for optical disk, cured product, and article therefrom

    JP2002265886A

  • Active energy ray-curable resin composition

    JP2012107118A

  • Photocurable resin composition and optical film obtained by using the same

    JP2014173072A